Recognising and Rewarding Leadership Roles in Transnational Education - Giridharan, Beena (Observatory of Borderless Higher Education, 2012)
Program coordinators and unit convenors involved in transnational education (TNE) represent a distributed group of leaders who often take on TNE coordination roles that can be challenging in cross-cultural settings. In their roles they are involved with colleagues from offshore branch campuses or partner institutions in the curriculum, delivery, and assessment and moderation of programmes. Both parties are concerned with achieving the course learning outcomes of the course while negotiating cultural and social contexts of learning in different campuses and countries. Therefore, the issue of recognition and reward for academics in TNE roles at home campuses and branch campuses is integral to the pedagogical and managerial success of the courses offered. This panel presentation highlights the broad outcomes and recommendations from an Australian Learning and Teaching ( ALTC) funded project entitled “Learning Without Borders: Linking Development of transnational leadership roles to international and cross-cultural teaching excellence” undertaken by a project team from two Australian universities with a branch campus each in Sarawak, Malaysia. TNE is defined in this Learning Without Borders project as an arrangement for provision of higher education where students in one country acquire an award which has been issued by a higher education institution based in another country.